Controlled dopamine (D1) receptor stimulation using photo-responsive substrates - Rajput, Sunil (2019)
Dopamine (2-(3,4-dihydroxyphenyl)ethylamine) is a key neurotransmitter involved in the formation of memory, and the process of learning. This is through the modulation of synaptic plasticity by the activation of cell surface receptors. The exact mechanism by which information from an external environment is processed and stored within our brain is still beyond our scientific knowledge. To determine how these processes work, we must first understand how a network of neurons communicates within a culture. In a model that enables development of our understanding of neuronal communication, continuous monitoring and stimulation of single cells using non-invasive methods is essential. For the development of this model, it is reasonable to treat monitoring and stimulation of cells as separate challenges. This thesis focuses on developing means that enable targeted stimulation of cells.